A Study of Leadership Competency of Student Leaders Participating in Extra-curricular Activities, Assumption University of Thailand - Kaipunlert, Tana (Scholar: Human Sciences, 2015)
This study was conducted to assess leadership competency of student leaders who participate in extracurricular activities throughout experiential learning approach provided by Assumption University of Thailand (Au). This study involved a sample of 242 student leaders of Au for the academic year 2008 taken from a population of 613 student leaders and in fact, there were 244 respondents who returned completed assessment using purposive random sampling technique. The instrument content was based on literature reviews and related researches. Assessments were used to identify two parts: demographic information and leadership competency in 5 dimensions of the Wagner‘s Leadership Competency Model (LCM) (2004), which apportions as follows: Self- Management, Leading Others, Task-Management, Innovation, and Social Responsibility as equally sustaining variables. The research found that the level of leadership competency of student leaders was at a strong level in all dimensions of Wagner‘s LCM.